Adolescence Amid a Pandemic: Short‐ and Long‐Term Implications. (26th August 2021) - Hussong, Andrea M.; Benner, Aprile D.; Erdem, Gizem; Lansford, Jennifer E.; Makila, Leunita Makutsa; Petrie, Rachel C.; ,
Abstract : Members of the Society for Research on Adolescents COVID‐19 Response Team offer this commentary to accompany this special issue of the Journal of Research on Adolescence regarding the impact of the pandemic on adolescents' social, emotional, and academic functioning. In addition to outlining the critical need for scholarly collaboration to address the global impact of this crisis on adolescent development, we argue that a broad investigative lens is needed to guide research and recovery efforts targeting youth development. We then use this broad lens to consider dimensions of the pandemic impact relative to developmental implications within community and policy contexts, educational contexts, social contexts, and family contexts. Finally, we describe guideposts for setting a global, shared research agenda that can hasten research to recovery efforts surrounding the pandemic and youth development.